Deep brain stimulation and sensorimotor gating in tourette syndrome and obsessive-compulsive disorder. (October 2020) - Schleyken, Sophia; Baldermann, Juan; Huys, Daniel; Franklin, Jeremy; Visser-Vandewalle, Veerle; Kuhn, Jens; Kohl, Sina
Abstract: Recent translational data suggest that deep brain stimulation (DBS) of the cortico-striato-thalamo-cortical (CSTC) loops improves sensorimotor gating in psychiatric disorders that show deficient prepulse inhibition (PPI), a robust operational measure of sensorimotor gating. To our knowledge we are the first to investigate this effect in patients with Tourette syndrome (TS). We measured PPI of the acoustic startle reflex in patients with TS (N = 10) or Obsessive-Compulsive Disorder (OCD) (N = 8) treated with DBS of the centromedian and ventro-oral internal thalamic nucleus and the anterior limb of internal capsule–nucleus accumbens area respectively, and aged- and gender-matched healthy controls (HC). PPI of the DBS groups was measured in randomized order in the ON and OFF stimulation condition. Statistical analysis revealed no significant difference in PPI (%) of patients with TS between ON (M = 20.5, SD = 14.9) and OFF (M = 25.2, SD = 29.7) condition. There were significantly reduced PPI levels in patients with TS in the ON condition compared to HC (M = 49.2, SD = 10.7), but no significant difference in PPI between TS in the OFF condition and HC. Furthermore, we found no significant stimulation or group effect for OCD and HC (OCD ON: M = 57.0, SD = 8.3; OCD OFF: 67.8, SD = 19.6; HC: M = 63.0, SD = 24.3). Our study has a number of limitations. Sample sizes are small due to the restricted patient collective. The study was not controlled for use of psychoactive medication or nicotine. Furthermore, we were not able to assess presurgical PPI measurements. In conclusion, we were able to show that PPI is impaired in patients with TS. This finding is in line with recent translational work. With respect to the OCD cohort we were not able to replicate our previously published data. A disability in sensorimotor gating plays a pivotal role in many psychiatric disorders therefore more research should be conducted to disentangle the potential and limitations of modulating sensorimotor gating via brain stimulation techniques. Highlights: Prepulse inhibition was impaired in patients with Tourette syndrome when DBS was on compared to controls. We found no evidence for an influence of DBS on prepulse inhibition in patients with Tourette syndrome. We found no evidence for an influence of DBS on prepulse inhibition in patients with Obsessive-compulsive disorder.